Breast conserving surgery and intra-operative specimen radiography: Margin assessment by the surgeon or the radiologist? - Senthurun Mylvaganam; Habib Tafazal; Virginia Caddick; Priya Madahar (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2018)
In the United Kingdom since the late 1990s there has been both a shortage of and falling level in recruitment of breast radiologists/radiographers. Specimen radiography is a widely used intra-operative adjunct to aid margin assessment in patients undergoing wide local excision for early stage breast cancer.  Aim: This study looks to determine accuracy and congruence of radiological intra-operative margin assessment by surgeon and consultant radiographer against the gold standard of histological assessment. Methods: Prospective assessment of specimen margins for all wide local excisions performed between June 2015 and June 2017 by a single breast surgeon in the UK. Specimen radiographs were independently assessed by a consultant radiographer and surgeon for adequacy of margins and compared to histological assessment.  Results: Both surgeon and consultant radiographer had an equal sensitivity of 33%, and specificity of 63% versus 73%. Negative predictive values were 89.2 (surgeon) vs 90.5 (radiographer). There was fair agreement between surgeon and radiographer (kappa= 0.252). Discussion: The accuracy of margin assessment by the radiologist in this study is similar to current literature. There is agreement between surgeon and radiographer and a high negative predictive value observed for both in x-ray interpretation suggesting equivalence of assessment and high confidence in evaluating negative margins. With the current UK trend of increasing radiology specific breast disease workload and recruitment deficit, a surgeon margin assessment only of the specimen x-ray may more optimally utilise radiology time without compromising re-operation rates.